2016
DOI: 10.18632/oncotarget.10868
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming chemoresistance in prostate cancer with Chinese medicine Tripterygium wilfordii via multiple mechanisms

Abstract: A leading cause of cancer chemotherapy failure is chemoresistance, which often involves multiple mechanisms. Chinese medicines (CM) usually contain multiple components which could potentially target many mechanisms simultaneously and may offer an advantage over single compounds that target one mechanism at a time. The purpose of this study was to investigate the chemosensitizing effect (CE) of a specific CM, Tripterygium wilfordii (TW), on prostate cancer cells resistant to docetaxel (Dtx) and identify the pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 47 publications
0
21
0
Order By: Relevance
“…Thus, careful in vivo efficacy with mechanistic study and concentration determination of the relevant compounds are important. In addition, the dose of DTX was chosen based on literature reports [ 17 , 54 ]. With regard to the dose of PIP, we firstly tried 100 mg/kg, the same dose as Makhov’s study in which PIP was used as a chemosensitizer to DTX [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, careful in vivo efficacy with mechanistic study and concentration determination of the relevant compounds are important. In addition, the dose of DTX was chosen based on literature reports [ 17 , 54 ]. With regard to the dose of PIP, we firstly tried 100 mg/kg, the same dose as Makhov’s study in which PIP was used as a chemosensitizer to DTX [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a synthesized naphthoflavone as CYP1B1 inhibitor could decrease the IC 50 of DTX in MCF7/1B1 cells [ 16 ]. Although Tripterygium wilfordii is attractive in combination DTX for potential mCRPC resistant to DTX, Tripterygium wilfordii as an extract has problem of quality control and therapeutic monitoring [ 17 ]. Therefore, a single natural compound which can overcome DTX resistance will be more attractive.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that the active ingredient extracts of TwHF also exhibit anti-tumour activities. Wang Z and colleagues found that TwHF seems to be able to sensitise resistant prostate cancer cells to the chemotherapeutic effect of docetaxel 14 .…”
Section: Introductionmentioning
confidence: 99%
“… Yang et al (2006) showed that celastrol is an effective natural protease inhibitor that induces prostate cancer cell apoptosis ( Li-Weber, 2013 ). A series of subsequent studies showed that celastrol exhibits pharmaceutical activities, such as anti-tumor, anti-rheumatism, analgesia activities ( Ríos, 2010 ; Kannaiyan et al, 2011 ; Wang et al, 2016 ). Moreover, there have been reported that celastrol is a leptin sensitizer and a promising agent for the pharmacological treatment of obesity ( Greenhill, 2015 ; Liu et al, 2015 ; Ma et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%